What is the solution to overcome the financial challenges of SMEs in Indonesia? Exploiting the potential of crowfunding in changing SMEs' financial landscape in Indonesia - Mohd Thas Thaker, Mohamed Asmy; Mohd Thas Thaker, Hassanudin (2015)
Small and medium enterprises (SMEs) have historically been considered as the main player in domestic economic activities, as they provide a large number of total business establishment, employment and hence generating primary or secondary source of income for many households including in Indonesia. However, with the financial crisis in 2008 started spreading around the world including in Indonesia, the access to early stage financing among SMEs has gotten significantly more difficult. Traditional banking mechanisms are unable to provide SMEs with the capital required to turn their ideas into reality. SMEs are considered as risky segment and various strict loan conditions have been imposed on them such as collateral requirement, stringent documentation requirement, high transaction costs, and good business and financial track record. Unfortunately, most of them cannot fulfill these conditions. As a result, SMEs had to look for other forms of alternative financing to fund their business. It was the purpose of this study to dive into a new paradigm of financing, in particular crowdfunding. Crowdfunding has been used as a way of financing and drawn the attention of various parties due to its growth potential and promptness in capital raising for new businesses including SMEs. Hence, the present study has used content analysis to critically look at the potential of crowdfunding in changing the SMEs’ financial landscape in Indonesia by highlighting its importance and possible application. Furthermore, market rejection due to the lack of the level of awareness and understanding of the public on crowdfunding are identified as one of the potential challenges that might arise in implementing crowdfunding. The research findings could also be used as part of the blueprints for the market players particularly SMEs and regulators to draft the necessary rules and regulations with regard to crowdfunding in Indonesia.